Pengaruh Profitabilitas dan Leverage terhadap Financial Distress: Pada Perusahaan Sektor Kesehatan yang Terdaftar di BEI Tahun 2019 -2023 - Renata Alissa Putri; Masriyanda Masriyanda; Silvi Reni Cusyana (Jurnal Riset Ekonomi dan Akuntansi, 2024)
In the current era of globalization, companies continue to refine their strategies and find opportunities to increase their advantages. For one, the healthcare sector has become a top priority for the Indonesian government. As a result, healthcare companies are increasing competition, forcing companies to adapt, improve their plans and performance, and capitalize on government initiatives to guarantee their survival. Companies that cannot compete and survive for long risk bankruptcy and eventual exclusion from the industry landscape. This study aims to analyze the effect of ROA and DAR on Financial Distress partially or simultaneously. This study uses secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange. This research method uses quantitative research methods using purposive sampling techniques with data processing using Excel and the SPSS 26 program. The total sample obtained was 10 health sector companies. The analysis method used is descriptive statistical test, classical assumption test, and hypothesis testing. The statistical model used is multiple linear regression analysis. The results of this study are (1) the ROA variable has a negative and significant effect on Financial Distress. (2) DAR variable has no effect on Financial Distress. (3) profitability and leverage variables on Financial Distress have a simultaneous effect.